One-pot synthesis of tunable crystalline Co3S4 @ amorphous MoS2 core/shell nanospheres for hydrogen evolution reaction - Gozal, Jennifer Claudia (2019)
MoS2 based electrocatalysts have recently received increasing attention as a substitution to platinum for hydrogen evolution reaction (HER). However, bulk MoS2 shows poor HER activity due to the lack of active sites. Previous studies shows that the intrinsic activity of the active sites can be improved by transition metal doping. From the volcano plot, we can see that cobalt is a promising doping due to its negative free energy (DGH < 0), which can neutralize the positive free energy (DGH > 0) of MoS2. Moreover, to increase the number of exposed sites for MoS2, we can tailor the nanoscale morphology to expose a greater catalytic active area. In this study, crystalline core-amorphous shell (Co3S4@MoS2) nanospheres has been synthesized with different Co/Mo ratios to understand the best composition to produce Co3S4@MoS2 with high HER activity. The study shows that Co3S4@MoS2 reduces the overpotential from 451mV to 175 mV and reduces the Tafel slope from 207mV/dec to 62 mV/dec if compared with pure MoS2, which leads to improved HER efficiency. However, the performance of the Co3S4@MoS2 is still far lower than that of Pt. Thus further optimization can be done to improve the catalytically active area of MoS2 to enchance the HER properties.